Analysis of laboratory tests results of patients submitted to a clinical screening program - Raphaela M. Zapelini; Kaiser S. Koch; Geraldo César C. Althoff; Camila S. Duarte; Eloysa M. João; Sérgio Silveira Jr
ABSTRACT Introduction: There are not studies demonstrating the major changes in biochemical tests performed in screening programs. Objective: Identify the results found in laboratory tests of patients submitted to medical check-up program, showing the main abnormal tests and correlating it with the age groups in which they were performed. Method: A cross-sectional study carried out with patients undergoing a screening service, from January to July 2015. Results: The study evaluated 738 patients. Form these, 53.3% were men and 46.7% were women. Body mass index (BMI) > 25 kg/m2 was present in 43.4% of patients aged 18-39 years; 46% aged 40-59 years and 10.5% aged ≥ 60 years. Levels of fasting plasma glucose between 100-125 mg/dl were found in 10.2%. Decreased levels of high-density lipoprotein cholesterol (HDL-c) were observed in 14% and high triglyceride values in 12.7%. Changes in blood count were found in 12.6%, 7.7% of which with anemia. Among the patients, 39% of had an qualitative urine testing (QUT). Of which, 21.2% presented microscopic hematuria. Glutamic-pyruvic transaminase (GPT) was decreased in 22.5%. Urea was increased in 11%. Vitamin D insufficiency and deficiency was present in 41.2% and 19.4%, respectively. Conclusion: The main biochemical tests that showed changes, in sequence, were: vitamin D; qualitative urine testing; GPT; HDL-c; triglycerides; blood count; fasting glycemia and urea. The only tests that had the most abnormal rates in young adults, aged 18-39 years, were: parasitological examination of stool; decreased serum levels of urea and glutamic-oxaloacetic transaminase (GOT) and increased values of GPT.